PENGEMBANGAN KOMPETENSI PEGAWAI MELALUI PENDIDIKAN DAN PELATIHAN DI BADAN KEPEGAWAIAN PENDIDIKAN DAN PELATIHAN KABUPATEN TIMUR - Imelda Juniar (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This is an author guidelines and article template of Jurnal paradigm. Article should be started by Title of article followed by Authors Name, Affiliation and abstract. This abstract section should be typed in font size of 10 pt and number of words of 150-200. English abstract should be written in italic. The single spacing should be used between lines in this article. Abstract is composed of: subject matter, purpose, method, result, and decision. Abstracts are written in the form of a single paragraph and one-column format, without reference, without acronyms, and without footnotes. Keywords: keywords, guideline, article